Prevalence of and risk factors for bovine respiratory syncytial virus (BRSV) infection in non-vaccinated dairy and dual-purpose cattle herds in Ecuador - Saa, L. (2017)
A cross-sectional study was carried out to determine the seroprevalence and risk factors associated with bovine respiratory syncytial virus (BRSV) infection in non-vaccinated dairy and dual-purpose cattle herds from Ecuador. A total of 2,367 serum samples from 346 herds were collected from June 2008 to February 2009. A questionnaire, which included variables related to cattle, health, management measures, and the environment, was filled out in each herd. Presence of antibodies against BRSV was analyzed using a commercial indirect ELISA test. A logistic regression model was used to determine risk factors associated with BRSV at herd level. The individual seroprevalence against BRSV in non-vaccinated herds in Ecuador was 80. 48% [1,905/2,367; 95% confidence interval (CI) = 78. 9-82. 1]. The herd prevalence was 91. 3% (316/346; 95% CI = 88. 3-94. 3), and the intra-herd prevalence ranged between 25% and 100% (mean, 90. 47%). The logistic regression model showed that the existence of bordering cattle farms, the dual-purpose farms, and the altitude of the farm (more than 2,338 m above sea level) were risk factors associated with BRSV infection. This is the first study about BRSV prevalence in Ecuador. It shows the wide spread of the BRSV infection in the country. The risk factors found will help to design effective control strategies. © 2012 Springer Science+Business Media B.V.